Bronchial responsiveness and the reproducibility of forced expiratory volume in one second. - Venables, K; Graneek, B; Taylor, A (1993)
Although poorly reproducible spirometric tests, "test failures," are associated with respiratory morbidity, it is not clear what causes them. Bronchial responsiveness was examined in relation to test failure for forced expiratory volume in 1 s (FEV1.0) (1979 definition of the American Thoracic Society) in 249 bakers, 165 chemical industry workers, and 204 office workers. The first two groups were studied by the same methods and were combined. Test failure was observed in 4%, and for 38% the provocative dose of inhaled methacholine causing a 20% fall in FEV1.0 relative to FEV1.0 after the inhalation of normal saline (PD20) was < or = 120 mumol (7% with a PD20 of < or = 8 mumol). Test failure was not related to the level of PD20. Of the office workers, 3% had test failure, 11% a PD20 of < or = 8 mumol of histamine, and no significant relation was observed. The study does not exclude the possibility that bronchial responsiveness might be related to test failure in patients with airway disease or that a clearer relation might be demonstrable in a larger study, but it does suggest that it is not a major determinant of test failure.